Improving the efficiency of the Fukui trap as a capture tool for the invasive European green crab (Carcinus maenas) in Newfoundland, Canada - Bergshoeff,Jonathan A.; McKenzie,Cynthia H.; Favaro,Brett (PeerJ, 2019)
The European green crab (Carcinus maenas) is a crustacean species native to European and North African coastlines that has become one of the world’s most successful marine invasive species. Targeted fishing programs aimed at removing green crabs from invaded ecosystems commonly use Fukui multi-species marine traps. Improving the efficiency of these traps would improve the ability to respond to green crab invasions. In this study, we developed four distinct trap modifications that were designed to facilitate the successful capture of green crabs, with the goal of improving the performance of the Fukui trap. We tested these modifications in situ during the summer of 2016 at two locations in Placentia Bay, Newfoundland. We discovered that three of our modified Fukui trap designs caught significantly more green crabs than the standard Fukui trap, increasing catch-per-unit-effort (CPUE) by as much as 81%. We conclude that our top-performing modifications have great potential for widespread use with existing Fukui traps that are being used for green crab removal efforts.
Keywords: Fishing gear; modification; AIS control; Catchability; Multi-species marine trap; Catch-per-unit-effort (CPUE); Invasive species; Crustacean; Portunidae; Green shore crab